Development of a process safety‐based, process design RAGAGEP for gas processing midstream facilities. Issue 3 (14th January 2021) - Aigen, Sam; Peters, Allison
Abstract: The fracking boom in the US led to an enormous task—the safe handling and processing of massive amounts of gas extracted as a byproduct of oil production. Process safety is often an afterthought in midstream operations since many midstream facilities are constructed and operated by the drilling companies which are excluded from PSM coverage by the oil and gas well drilling and servicing exemption, 29 C.F.R. §1910.119(a)(2)(ii). Nonetheless, many midstream companies have begun to apply the best practice of conducting process hazard analyses (PHAs) and layer of protection analyses (LOPA) on PSM and non‐PSM covered facilities alike, to improve company process safety and operational integrity. However, if company internal standards are not applied, the application of extensive process safety practices that were originally intended for larger operations such as refineries could impede the adoption of process safety, and may lead to inefficient use of time and resources. This paper will look at actual examples of how one major midstream company developed an internal design standard that could be used toward the development of a midstream gas processing‐specific process design RAGAGEP. The objective of this RAGAGEP would be to streamline design, simplify risk assessments/hazard analyses and improve efficiency and consistency of process safety implementation.